THE EFFECTIVENESS OF THE ROLE OF THE MEDIATOR IN THE EQUITABLE SETTLEMENT OF INDUSTRIAL RELATIONS DISPUTES - Sugiyanto Sugiyanto (Universitas 17 Agustus 1945 Semarang, 2021)
The State of Indonesia is obliged to regulate Mediators to effectively settle industrial relations disputes through a sound industrial relations system. The industrial relations system formed between the actors in producing goods and services is expected to create harmonious and just industrial relations. The problems in this study are; (1) What is the role of the mediator in creating harmonious industrial relations? (2) How is the effectiveness of the mediator’s role in the fair settlement of industrial relations disputes? This research method uses normative juridical, a study that is very closely related to primary data in the form of related laws and regulations, and secondary data in the form of literature books. The approach method used in this research is empirical juridical. Juridical research is the law which is conceptualized as the effectiveness of the mediator’s role in the fair settlement of industrial relations disputes. The results showed that; (1) The role of mediator in creating harmonious industrial relations by providing understanding to workers and employers regarding labor regulations to create harmonious industrial relations. The role of the industrial relations mediator is preventive or preventing industrial relations disputes from occurring. (2) The effectiveness of the mediator’s role in the just settlement of industrial relations disputes must guarantee a fair and effective settlement of industrial relations disputes. In a fair and effective settlement of industrial relations disputes, the ideal mediation is resolved by a fair and non-discriminatory institution. The disputing parties can choose a mediator deemed the neutral parties capable of doing justice and fair settlement procedures.